Spiritual Ends: Religion and the Heart of Dying in Japan - Ivry, Benjamin (Thai Journal of East Asian Studies, 2025)
This publication by Assistant Professor Timothy O. Benedict, who teaches in the School of Sociology at Kwansei Gakuin University, Japan, is an ethnographic case study and memoir. It is based on interviews with hospice patients and workers, compiled when the author served as a chaplain at a Presbyterian hospital in western Japan between 2009 and 2011. These origins give an inescapably Christian outlook to a research work about a country, most of whose inhabitants adhere to Shintoism. Assistant Professor Benedict maintains an empathetic tone in his descriptions of the bafflement expressed by patients confronted with his essentially Christian approach to counseling. He stresses that Japan as a super-aging society where the birthrate is in decline will require caregivers to assist aged persons at the end of their lives. This role may be fulfilled by hospices, which try to preserve a sense of patient individuality and personhood, or kokoro (heart, spirit, mind, wisdom, aspiration, essence, attention, sincerity and sensibility). In addition, hospice chaplains may increasingly serve a population without many affinities to traditional organized religion, as usually defined in theistic societies.